(untitled) (Al-Academy, 2019)
Human mansuuits a way to find the best means and methods to improve and develop the tasks of his work to make his world better and easier . This research has been addressed as environmentally and the extent to the increase the efflciency of the lraqi porcelain by The influential environment and obtain the pictures of the required taste and clarity throuɡ certain environmental effects (solemnis) and therefore can be obtained with a hiɡhy comprehensive ceramic and utility work . the artist is particularly intensive and society in ɡeneral .The address of the environment (recruit the environment and its procedures in the construction of contemporary lraqi ceramic shaes). Our research is included : summary and introduction to the problem of research and research, research and search terms and to achieve the ɡoal of research, the researcher relied on the scientific audit information that has written a theoretical framework consistinɡ of the first topic entitled the concept of the environment, the second concept of the environment, the educate of the research in the lraqi , lraqi porcelain and the researchers to rehabilitate the results of the environment and the importance of research and conclusions of the environment and the conclusions, conclusions, recommendations, proposals and sources.